2022
DOI: 10.34190/ictr.15.1.132
|View full text |Cite
|
Sign up to set email alerts
|

Developing Hospitality Management Core Competencies Framework

Abstract: Developing a unique set of Core Competencies should be of primary concern to any business operating in the hospitality industry. This paper presents a framework for competency development, which is based on the views of both educators and industry professionals. By integrating knowledge from a variety of contexts and countries around the world, a set of generic core competencies has been derived via a systematic classification process. Specifically, forty competency statements have been posited taking the form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
1
0
2
Order By: Relevance
“…Conversely, it was observed that staff in the tourism sector are key determinants of the variables such as service quality, customer satisfaction and loyalty, competitive advantage and organizational performance (Abdiyev & Alimardonov, 2022;Kalla;Wang, Ban, Joung, & Kim, 2022). Also, it was found that the quality of human resources plays a crucial role in determining the quality, delivery, efficiency, and satisfaction of services offered (Marneros, Papageorgiou, & Efstathiades, 2022). Furthermore, it was observed that world-widely, the ability of human resources to deliver quality services is a major source of competitive advantage (Batat, 2022;Charusalaipong, 2022).…”
Section: Training Needs Assessment In the Tourism Industrymentioning
confidence: 99%
“…Conversely, it was observed that staff in the tourism sector are key determinants of the variables such as service quality, customer satisfaction and loyalty, competitive advantage and organizational performance (Abdiyev & Alimardonov, 2022;Kalla;Wang, Ban, Joung, & Kim, 2022). Also, it was found that the quality of human resources plays a crucial role in determining the quality, delivery, efficiency, and satisfaction of services offered (Marneros, Papageorgiou, & Efstathiades, 2022). Furthermore, it was observed that world-widely, the ability of human resources to deliver quality services is a major source of competitive advantage (Batat, 2022;Charusalaipong, 2022).…”
Section: Training Needs Assessment In the Tourism Industrymentioning
confidence: 99%
“…Để đảm bảo việc có thể làm việc được trong ngành nghề du lịch cần phải cân bằng giữa hai loại kỹ năng bắt buộc là kỹ năng cứng và kỹ năng mềm, tuy nhiên kỹ năng mềm có thể xem là quan trọng hơn [7]. Việc phát triển một bộ năng lực cốt lõi đối với ngành nghề luôn là mối quan tâm hàng đầu của bất kỳ tổ chức nào trong lĩnh vực du lịchkhách sạn và cần được xem xét ở cả hai khía cạnh của các nhà giáo dục và chuyên gia trong ngành [8]. Do đó, các đơn vị sử dụng lao động bên cạnh việc đánh giá những kiến thức chuyên môn của ứng viên sẽ chú trọng nhiều vào tính chất từng công việc, một số kỹ năng mềm được trang bị sẽ là nhân tố quan trọng để đánh giá hiệu quả công việc.…”
Section: Giới Thiệuunclassified
“…Nó là những thuộc tính cá nhân giúp cải thiện sự tương tác của cá nhân và khả năng thực hiện một công việc cụ thể [3]. Stelios Marneros và cộng sự [8]thì cho rằng, năng lực bao gồm những kỹ năng cần thiết cho ngành nghề như là: giao tiếp hiệu quả với khách hàng, nhận diện và giải quyết vấn đề, ra quyết định trước các tình huống áp lực và khủng hoảng, và hiểu được các yếu tố ảnh hưởng đến lợi nhuận của tổ chức.…”
Section: Vai Trò Của Kỹ Năng Mềm đốI Với Các Ngành Du Lịchunclassified